A taxonomic revision of the squat lobsters (Anomura: Chirostyloidea and Galatheoidea) of South Africa - Botha, Thomas (Department of Biological Sciences, 2025)
South African squat lobsters (Chirostyloidea and Galatheoidea) are a severely understudied group. They have never been the subject of a formal monographic study and the last additions to the fauna were made almost 20 years ago. Thus, a revision of these superfamilies is long overdue. This study relied on examination of historic material housed in the Natural History Collections of the Iziko South African Museum, as well as ad-hoc sampling to carry out morphological analyses and molecular barcoding where possible. These methods were used to add to, revise and update the regional fauna. The thesis is presented in the form of six chapters, four of which each revise one of the families of squat lobsters present in South Africa and provide an illustrated key to the known regional species in that family. These chapters are supported by an introduction and synthesis chapter and a reference list. The first revisory chapter covers the Chirostyloidea (Chapter 2), and includes redescriptions of four species, reports on one species (and genus) from South Africa for the first time and expands the distribution and depth range for Uroptychus simiae. The third chapter describes two new species of Galatheidae, adds three species (and a genus) to the regional fauna list and resolves several dubious records. Galathea labidolepta Stimpson, 1858 is also redescribed and a neotype assigned, as the holotype was lost in the 1871 Chicago fire. The Munididae are revised in the fourth chapter, wherein two new species are described, seven species (four of which are new generic records for South Africa) are added as new distribution records, while five species are redescribed, two of which were previously only known from brief descriptions. The fifth chapter revises the deep-dwelling Munidopsidae and redescribes two species. This study marks the largest ever contribution to the South African squat lobster fauna with 15 species being added, comprising four new species and 11 new distribution records, while two species are removed due to synonymy. This increases the number of South African squat lobster species from 32 to 45. In the process, six genera are also reported on for the first time. Illustrated redescriptions are given for 12 species that were known from outdated or inadequate descriptions. Where possible, DNA sequences were produced as part of an integrative approach to delineate species, and this is the first study to provide such genetic data on South African squat lobsters, with 28 barcodes provided for eight species. Though this study adds valuable knowledge to this important group, it also highlights the need for more rigorous sampling, as more than half of the species are known from just a single sampling event and almost certainly more species remain to be discovered from the region.